Emerging Need for PROMs to Measure the Impact of Spine Disorders on Overall Health and Well-being: Measuring Expectations as an Example for Lumbar Degenerative Spondylolisthesis. Issue 2 (May 2023) - Duculan, Roland; Fong, Alex M.; Cammisa, Frank P.; Sama, Andrew A.; Hughes, Alexander P.; Lebl, Darren R.; Farmer, James C.; Huang, Russel C.; Sandhu, Harvinder S.; Mancuso, Carol A.; Girardi, Federico P.
Background: Assessing the impact of spine disorders such as lumbar degenerative spondylolisthesis (LDS) on overall health is a component of quality of care that may not be comprehensively captured by spine-specific and single-attribute patient-reported outcome measures (PROMs). Purpose : We sought to compare PROMs to the Lumbar Surgery Expectations Survey ("Expectations Survey"), which addresses multiple aspects of health and well-being, and to compare the relevance of surgeon-selected versus survey-selected Patient-Reported Outcomes Measurement Information System (PROMIS) items to LDS. Methods : In a cross-sectional study, 379 patients with LDS preoperatively completed the Expectations Survey, Numerical Rating Pain Scales, Oswestry Disability Index (ODI), and PROMIS computer-adaptive physical function, pain, and mental health surveys. Expectations Survey scores were compared to PROMs with correlation coefficients (indicating strengths of relationships) and probability values (indicating associations by chance). Surgeons reviewed physical function questions to identify those particularly relevant to LDS. Results : Patients' mean age was 67 years, 64% were women, and 83% had single-level and 17% had multiple-level LDS. Probability values between the Expectations Survey and PROMs were reliable, but strengths of relationships were only mild to moderate, indicating PROMs did not comprehensively capture the impact of LDS. None of the surgeon-selected PROMIS physical function questions were posed to patients. Conclusion : This cross-sectional study found PROMs to be reliably associated but not strongly correlated with the Expectations Survey, which addresses the whole-patient impact of LDS. New measures that complement PROMIS and ODI should be developed to capture the whole-person effects of LDS and permit attribution of LDS treatments to overall health.